2019
DOI: 10.1002/eap.1980
|View full text |Cite
|
Sign up to set email alerts
|

Modeling variability in the fire response of an endangered bird to improve fire‐management

Abstract: Conservation managers regularly burn vegetation to regenerate habitat for fire-dependent species. When determining the time since fire at which to burn, managers model change in a species' occurrence over time, post-fire (fire-response curve) and identify the time since fire associated with decline in occurrence. However, where species exhibit variability in their fire response across space, using a single fire-response curve to determine the timing of burns may lead to burning habitat at an inappropriate time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 67 publications
(173 reference statements)
1
11
0
Order By: Relevance
“…Similar patterns to those shown here have been observed previously in temperate eucalypt forests (Swan et al 2015, Haslem et al 2016) and mallee woodlands (Haslem et al 2011). Understorey vegetation provides nesting, foraging and shelter sites for many bird and mammal species typical of these and similar ecosystems (Ford et al 1986, Fox et al 2003, Simonetti et al 2013, Swan et al 2015, Verdon et al 2019. Consequently, the temporal responses of such faunal species to fire are likely to be positively influenced by these post-fire trajectories in habitat suitability (e.g.…”
Section: Author Manuscriptsupporting
confidence: 84%
“…Similar patterns to those shown here have been observed previously in temperate eucalypt forests (Swan et al 2015, Haslem et al 2016) and mallee woodlands (Haslem et al 2011). Understorey vegetation provides nesting, foraging and shelter sites for many bird and mammal species typical of these and similar ecosystems (Ford et al 1986, Fox et al 2003, Simonetti et al 2013, Swan et al 2015, Verdon et al 2019. Consequently, the temporal responses of such faunal species to fire are likely to be positively influenced by these post-fire trajectories in habitat suitability (e.g.…”
Section: Author Manuscriptsupporting
confidence: 84%
“…The subdued topography of mallee ecosystems and their nutrient-poor soils appear to offer little in the form of permanent drought refuges. Nevertheless, there remains much to learn about how variation in habitat suitability is associated with topography (Selwood et al, 2019;Verdon et al, 2019). Much will depend on a species' ability to move between resources (Nimmo et al, 2019), and whether habitat connectivity enables such movement.…”
Section: Fire Dangermentioning
confidence: 99%
“…Our data are broadly consistent with this hypothesis, but also show that the actual time depends on site and context and, for the FRNP, is likely to be at the long end of this spectrum. There could be multiple factors influencing the actual time; for example, Verdon et al (2019) have shown that elevation and time since fire interact to affect fire response in the Mallee Emu-wren Stipiturus mallee. In the case of the Western Bristlebird, the optimal interval is likely to be considerably longer in low-rainfall areas such as around Fitzgerald Track (northern area of the FRNP), and there can be variation within such areas.…”
Section: How Do Western Bristlebirds Survive a Fire Event?mentioning
confidence: 99%
“…Threatened species that have specific requirements for fire age in their habitat are the ones likely to suffer the most from inappropriate fire regimes, and management is complicated when co-occurring species have stringent but different requirements in relation to fire (Kelly et al 2015;Woinarski et al 2015). Fire management is further complicated where the optimal time since fire for habitat to regenerate varies according to environmental conditions or habitat parameters (Verdon et al 2019). It becomes even more challenging where there have been large changes in land use with consequent habitat loss, and fire regimes (fire extent, intensity, seasonal timing and frequency) are also changing in relation to ongoing climate change, such as in south-western Australia (Abbott & Burrows 2003;Mariani et al 2018).…”
Section: Introductionmentioning
confidence: 99%